Opportunities, Constraints and Strategic Interventions in Onion Value Chain: The Case of Ambo and Toke Kutaye Districts, West Showa Zone, Oromia Regional State, Ethiopia - Shiferaw, G Diriba; Mentafa, H Birhanu; Milkessa, Temesgen (Journal of Postharvest Technology, 2017)
Onion crop is one of the most important vegetables produced in Ethiopia for both commercial and consumption purposes. However, due to different constraints the potential of the crop was not utilized to the fullest extent by economic entities along the commodity chain. Thus, the study was conducted in order to assess the opportunities, constraints and to develop strategic interventions in onion production and value chain in Ambo and Toke Kutaye districts of West Showa Zone, Oromia Regional State, Ethiopia in the year 2015 with the objective of identifying the constraints and opportunities for onion value chain functions in the study areas. From the districts, seven onion producing kebeles were selected randomly and the data were collected from both primary and secondary sources. The primary data were collected using interview guided questionnaires from 183 respondents’ of different actors in onion value chain and four focus group discussions of onion producers. Descriptive statistics and value chain analysis were used to analyze the constraints and opportunities data. Onion value chain in the area contains different actors at the stages of input suppliers, onion producers, wholesalers, retailers and consumers. Thus, diseases, drought, insects, lack of sufficient irrigation water, limited supply of agricultural inputs, limited knowhow and skill, low price of produce and poor linkage with value chain actors were major producers’ constraints identified in the study areas. Supply shortage, lack of organized market information, low produce quality, loss of produce due to poor handling, competition with unlicensed traders, price fluctuation and lack of support from government bodies were major marketing constraints studied on the traders. Thus, onion value chain is affected by several aforementioned constraints at each stage of the chain functions those influenced the efficiency and competitiveness of the whole chain in the study areas. The recommendations forwarded to accelerate the onion value chain’s development are strengthening extension system and other supportive services; supporting producers in order to use improved agricultural inputs, modern technologies, controlling diseases and insects (pests) problems; constructing additional irrigation facilities/schemes; organizing, strengthening and supporting vegetable producer cooperatives and controlling unlicensed traders.